Dakwah Humanis melaui Gerakan Tarekat - Qomariah Moehson (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2019)
Humanist propaganda is one way of da'wah with the aim of making humanity. Tarekat is a religious activity which is important for Muslims to draw closer to Allah SWT. The purpose of this study is to analyze the da'wah process through tarekat activities which are considered to have strategic content values in making Muslims better. This study was conducted with a phenomenological qualitative approach. The results of this study reveal that preaching activities through tarekat are good Da'wah choices. The goodness of da'wah through the tarekat is seen as more about the target, where the members of the tarekat are more concerned about their whereabouts, at the same time the members or congregations are also given da'wah material in accordance with their wishes and existence. Dakwah humanis merupakan salah satu cara dalam berdakwah dengan tujuan lebih menjadikan manusia secara lebih manusiawi. Tarekat merupakan sebuah kegiatan keagamaan yang dipandan penting bagi umat Islam dalam mendekatkan diri kepada Allah SWT. Tujuan penelitian ini melakukan analisis terhadap proses dakwah melalui kegiatan tarekat yang dipandang mempunyai nilai kandungan strategis dalam menjadikan umat Islam menjadi lebih baik. Studi ini dilakukan dengan pendekatan kualitatif fenomenologis. Hasil penelitian ini mengungkapkan bahwa kegiatan dakwah melalui tarekat merupakan pilihan dakwah yang baik. Kebaikan dakwah melalui tarekat dipandang lebih mengenai pada sasaran, dimana anggota tarekat lebih diperhatikan keberadaannya, sekaligus para anggota atau jamaah tarekat juga diberi materi dakwah yang sesuai dengan keinginan dan keberadaan dirinya.